Analisis Faktor Penerimaan Layanan e-Government dengan Menggunakan Model UTAUT2 dan GAM di Kabupaten Gunungkidul - Eko Setiawan; Wing Wahyu Winarno; Dhomas Hatta Fudholi (STMIK Budi Darma, 2021)
Government through Presidential Regulation No. 95 of 2018 concerning SPBE supports and realizes clean, effective and transparent government governance so that it has quality and trusted public services. To improve society using e-government based services, it is necessary what factors influence a person to use e-government services. This study uses the UTAUT2 research model and the Government Adoption Model (GAM) to determine the factors that influence a person using e-government in Gunungkidul. This study used the PLS SEM measurement method and found that the factors that influence e-government acceptance are effort expectation, facilitating conditions, and computer self-efficacy.